2001
DOI: 10.1038/sj.jea.7500165
|View full text |Cite
|
Sign up to set email alerts
|

The National Human Activity Pattern Survey (NHAPS): a resource for assessing exposure to environmental pollutants

Abstract: Because human activities impact the timing, location, and degree of pollutant exposure, they play a key role in explaining exposure variation. This fact has motivated the collection of activity pattern data for their specific use in exposure assessments. The largest of these recent efforts is the National Human Activity Pattern Survey ( NHAPS ), a 2 -year probability -based telephone survey ( n = 9386 ) of exposure -related human activities in the United States ( U.S. ) sponsored by the U.S. Environmental Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
2,035
4
16

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 3,632 publications
(2,247 citation statements)
references
References 25 publications
(27 reference statements)
28
2,035
4
16
Order By: Relevance
“…Detailed survey methodology of the two surveys has been previously published (Klepeis et al, 2001;Leech et al, 1996;Nelson et al, 1996;Tsang and Klepeis 1996 ).…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed survey methodology of the two surveys has been previously published (Klepeis et al, 2001;Leech et al, 1996;Nelson et al, 1996;Tsang and Klepeis 1996 ).…”
Section: Methodsologymentioning
confidence: 99%
“…While several approaches to recording time -activity data have been used, ranging from self -administered recall to directly supervised observation, the 24 -h recall diary has found general acceptance after its application by the California Air Resources Board for exposure assessment (Wiley et al, 1991 ). Using a similar 24-h recall diary the United States' Environmental Protection Agency undertook a random sample telephone survey of the time and activity patterns throughout the continental USA in 1992 to 1994, the National Human Activity Pattern Survey ( NHAPS ) (Klepeis et al, 2001 ). This study compares the NHAPS results to a survey using the same methodology in a smaller random sample within four Canadian cities in 1996-1997, the Canadian Human Activity Pattern Survey ( CHAPS ) (Leech et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…When dealing with transient peaks of environmental contaminants, knowing whether or not a person is in a particular microenvironment is the first step toward determining if exposure may occur (Klepeis et al, 2001;McCurdy and Graham, 2003). Time-location has been measured using self-report diary instruments for many years (Robinson, 1988;Wallace et al, 1987Wallace et al, , 1991Freeman et al, 1993Freeman et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects reported spending 75% of waking hours indoors and 11% in vehicles; these would approximate to 87% and 7%, respectively of a 24-h period. This time indoors for example would be similar to, but the time in vehicles would be greater than, NHAPS data (Klepeis et al, 2001).…”
Section: Introductionmentioning
confidence: 86%
“…Random sample populations in California (Wiley et al, 1991), the continental USA (National Human Activity Pattern Survey or NHAPS) (Klepeis et al, 2001), and Canada (Canadian Human Activity Pattern Survey or CHAPS) (Leech et al, 1996) have used this method; comparisons have shown very little difference in time and activity patterns over 24 h in normal subjects in these populations (Leech et al, 2001;Johnson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%